Effect of commercial and green synthesized ZnO NPs in murine model of chloroquine-induced pruritus - Aman N; Rauf K; Khan SA; Tokhi A; Rehman NU; Yameen MA (International Journal of Nanomedicine, 2019)
Nargis Aman, Khalid Rauf, Shujaat Ali Khan, Ahmed Tokhi, Naeem-Ur Rehman, Muhammad Arfat YameenDepartment of Pharmacy COMSATS University Islamabad, Abbottabad Campus, Abbottabad, KPK, PakistanPurpose: To investigate the effects of zinc oxide nanoparticles (ZnO NPs) on chloroquine (CQ)-induced itching, and overall behavior of mice after oral administration of ZnO NPs of various sizes and doses.Background: With the wide-spread use of ZnO NPs in pharmaceuticals and cosmetics, concerns about their safety and toxicity are also increasing. Multiple aspects of ZnO NPs regarding cytotoxicity and tolerability are under investigation globally. Still, a clear conclusion about their safety has not been reached. Chloroquine phosphate is an antimalarial with known side effects of itching in humans and animals. In this study, CQ was used to induce itching in mice, and the effects of ZnO NPs on scratching and other neurological behavior of mice were observed.Methods: Female BALB/c mice were divided into eleven groups of six mice each. ZnO NPs of various sizes and doses were administered orally 1 hour before CQ (32 mg/kg body weight) was administered subcutaneously. The effect of ZnO NPs on CQ-induced pruritus was observed for the next 30 minutes. Simultaneously, overall behavioral changes (socialization and locomotion) were also recorded using a video camera.Results: A significant reduction (P˂0.001) in scratching bouts was observed at all three doses of ZnO NPs (particle sizes 100, 30 nm, and green synthesized 30 nm). Locomotion was reduced significantly (P˂0.001) in ZnO NPs-treated groups in comparison to normal saline and CQ group, additionally, a significant increase in socialization (P˂0.05) was observed in ZnO NP-treated groups as compared to CQ group.Conclusion: ZnO NPs, instead of aggravating the dermatological condition, ameliorated the pruritus. All sizes of ZnO NPs used significantly improved socialization among mice and reduced locomotion activity.Keywords: ZnO NPs, chloroquine-induced pruritus, CQ, green synthesized ZnO NPs, mice